Tumbuhkan Karakter Cinta Rasul: Pendampingan Pelestarian Budaya Islam melalui Jam’iyah Dibaiyah - Saputra, Doni (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This study explores efforts to cultivate the character of love for the Prophet Muhammad SAW through a cultural preservation program among women in Dusun Ngandong, Kediri, with a focus on the Jam’iyah Dibaiyah activities. This initiative is driven by the importance of preserving Islamic traditions while strengthening religious identity in communities with minimal religious activities. The program involves revitalizing the tradition of reciting shalawat through Jam’iyah Dibaiyah, conducted regularly. The implementation began with mapping the community's condition, followed by consultations with local religious leaders, and organizing Jam’iyah Dibaiyah activities at various agreed locations. Evaluation of the program shows a significant increase in religious knowledge, active participation of women, and the reinforcement of love for the Prophet Muhammad SAW. Additional positive impacts include strengthened social bonds and solidarity among community members, improved religious understanding and skills, and changes in attitudes and behaviors aligning more closely with Islamic teachings. The program effectively created change agents within the community, making women role models in instilling Islamic values within their families and the surrounding community. This study highlights the importance of collaboration between the community and facilitators in sustaining religious empowerment efforts.